Coordenação intergovernamental em políticas públicas: programa de aquisição de alimentos - Oliveira, Neuza Corte de (2017)
Generally speaking, in countries like Brazil, where there is a lot of inequality in income distribution, the constitutional arrangement of Federation adopts the principle of responsibility for the provision of most public services, particularly in the area of social policies, common to the three levels of Government. In this sense, the institutional design of intergovernmental relations between the different levels of Government can be understood as a set of mechanisms and strategies to induce the Government to adhere to national public policies. Thus, this paper seeks to analyse the forms of interaction between the three governmental spheres in Brazil looking particularly the food acquisition Program in purchase mode with simultaneous donation, mixed model. The choice of this empirical object is justified not only by your social importance in the fight against extreme poverty in the country, but above all by the fact become public policy whose implementation is done by the performance. To meet the proposed in the study, the methodological strategy adopted was the single case study, that allows to explain the causal links in speeches or real life situations too complex to be handled through experimental strategies or broader comparisons of data that require deepening of various levels of analysis, adopting a combination of techniques or information sources to validate the results , such as laws, decrees, resolutions, reports, minutes of meetings, interviews and direct observation. The choice of the State of Paraná and the municipality of Maringá as the locus of empirical research was made for practical reasons that facilitate the collection of information. As the research reinforces findings the literature of the existence of a pattern of interdependent relationship in the implementation of a public policy is key to your success. However, points out that the agreements between the spheres of Government are essential to achieve the goal outlined in the design of policy. Thus, the independent authority of Wright (1988), exists between Governments a total independence and autonomy relationship, which would be achieved from the complete clarification of the roles of each of the spheres of Government. Therefore, the type of hierarchical authority, modelizado by Wright, requires the implementation of shared public policy, a clear delineation of the roles of each sphere of Government. On the other hand, are not sufficient the delimitation of roles in the three spheres of Government, it is necessary to be clear policy objectives for implementers and what's expected of them. These issues are linked to a greater or lesser possibility of resistance to the plan. Add to that the forecast and availability of resources, especially financial. It is concluded that the hypothesis on which the investigation the ‘failure’ or the impossibility of the food acquisition Program (PAA) to intergovernmental relationship – demand taken as needed so that it reaches your goals – is due to the absence of an interdependent relationship pattern (or of bargaining) between his actors is proven by research.